FREQUENCY OF POST-OPERATIVE ATRIAL FIBRILLATION IN PATIENTS UNDERGOING CABG PROCEDURES - Khan, Hira; Azad, Naseem; Iftikhar, Shazmeena; Rehman, Muneeb -Ur-; Nafees, Shahid; Afzal, Hira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of post-operative atrial fibrillation (POAF) in patients undergoing on-pump coronary artery bypass grafting (CABG).Study Design: A descriptive cross-sectional study.Place and Duration of Study: Adult Cardiac Surgery department, AFIC/NIHD, Rawalpindi, from Sep 2019 to Jan 2020.Methodology: This study was conducted on 80 cardiac patients fulfilling the inclusion criteria among the patients underwent CABG surgery. They were observed during the hospital stay for the development of AF. Data was analyzed using SPSS-23 and p≤0.05 was taken as statistically significant.Results: In this study, 80 patients who underwent ON-PUMP CABG. The frequency of POAF calculated is 47 (58.75%). Majority of the patients who developed POAF presented with history of hypertension and diabetes mellitus i.e.27.50% with male predominance i.e. 70% with the mean of variables, age=60.19 ± 9.3 years, body mass index=28.27 ± 4.2 kg/m2, CPB time = 156 ± 39.7 min, aortic cross-clamp time=100 ± 27.2 min, ejection fraction v(EF) = 47.2 ± 10.7%, heart rate = 117.8 ± 21 beats per minute and serum lactate levels = 3.7 ± 1.54 mmol/lit. Also mortality rate was seen relatively higher in patients with POAF i.e. 30 (38%) than in those having no POAF i.e. 50 (62%).Conclusion: Frequency of POAF is moderately high with advanced age. Hypertension, obesity and BMI plays pivotal role in the development of POAF with prolong bypass time and Aortic Cross-clamp time. AF caused raised heart rate and serum lactate levels alongside compromised heart function, increased mortality and hospital stay.